PELAKSANAAN PELATIHAN BAGI PENDIDIK UNTUK MEMENUHI STANDAR KOMPETENSI JENJANG SD DI KOTA PEKANBARU - Eunike Daniella Pinem; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The large number of schools in Pekanbaru, of course, also has a large number of students. To provide a decent and quality education, of course, it must be balanced with the number of adequate and competent teachers. The Pekanbaru city education office is an institution that regulates the course of education in the city of Pekanbaru. The Pekanbaru City Education Office makes a program to improve the quality of educators at the basic education level, one of which is training for educators to meet competency standards. The concept used is Prajudi Admosudirdjo, namely there are four indicators: Planning, Organizing, directing, Supervising. This study uses a qualitative research type with a phenomenological approach and the required data, both primary and secondary, are obtained by using observation, interview and documentation techniques. inhibiting factors in the implementation of training for educators to meet competency standards, namely: there are still many passive trainees during training, internet connection is less stable during virtual training then difficulty in dividing task groups during virtual training and other factors are budget. The budget that should be used for the implementation of this training program is used for vaccination activities for teachers and students in the city of Pekanbaru  Keywords: Implementation, Quality Improvement, Training Program